The Impact of Service Quality and Accessibility on Customer Loyalty: The Mediating role of Customer Satisfaction - Adelia, Lisa; Purnama, Eka Desy (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to examine the influence of service quality and service accessibility on customer loyalty, with customer satisfaction as a mediating variable. The research was conducted at RSUD dr. Chasbullah Abdulmadjid, Bekasi City, focusing on outpatients using clinical laboratory services with general or private payment schemes. Data were collected through structured questionnaires from 210 respondents selected using purposive sampling, based on criteria such as being at least 18 years old and having used the laboratory service at least once in the past year. The analytical method employed is Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess both direct and indirect effects among variables. The results show that service quality significantly affects both customer satisfaction and loyalty, and customer satisfaction is confirmed to mediate the relationship between service quality and loyalty. Meanwhile, service accessibility has a significant direct effect on customer loyalty but does not significantly influence customer satisfaction, nor is it mediated through satisfaction. These findings highlight the dominant role of service quality in driving satisfaction and loyalty, while accessibility contributes to loyalty more directly. Hospitals and service providers are encouraged to prioritize service quality while maintaining adequate accessibility, adopting a comprehensive strategy to enhance the overall patient experience and foster sustainable customer loyalty.